IMPROVING STUDENTS’ WRITING RECOUNT TEXT ACHIEVEMENT THROUGH MIND MAPPING TECHNIQUE AND JOURNAL AT SMA KORPRI BANJARMASIN SCHOOL YEAR 2016/2017 - Sahli, Ali (Journal Compound: Improving the Quality of English Education, 2021)
This research was a collaborative classroom action research study which happened in two cycles. This research aimed to explore whether the students achieve better score in writing a recount text for the eleventh grade students after they taught by using mind mapping and journal at SMA KORPRI Banjarmasin school year 2016/2017. The researcher used qualitative and quantitative data. Qualitative data were obtained through the interview with the English teacher and the students and the classroom observation during the teaching and learning process. Meanwhile, the quantitative data were the results of the students’ writing before the implementation of the actions (pre-test), while the actions (progress test), and after the implementation of the actions (post-test). The results showed that mind mapping technique and journal helped the teacher in writing class. The result of the interview with the teacher and students showed that the students’ writing ability was improved. The class percentage of posttest showed some improvements for the previous test; the improvement was 54.8395% from the pretest (3.225%) or 29.025% (32.25% - 3.225%). Automatically, it can be said that the Classroom Action Research (CAR) was succeed.